Application of the Radec Learning Model to the Science Learning Outcomes of Grade IV Elementary School Students - Riska Aulia; Dian Samitra; Sujarwo Sujarwo (CV. Edujavare Publishing, 2026)
Learning occurs through the process of interaction between students and educators and learning resources in a learning environment. This study aims to determine the completeness of student learning outcomes after the application of the RADEC Learning Model in the subject of Science for Grade IV Students of SD Negeri 72 Lubuklinggau. This research method uses a quantitative approach with a quasi-experiment using a pre-test and post-test research design. Using multiple choice questions totaling 18 questions. The research sample was grade IV consisting of 24 students. The research data analysis technique used a normality test and a Z-test with a confidence level of 5%. The results showed that based on data analysis, it was known that the results of the initial ability test (pre-test) had an average of 47.12 and the final ability test (post-test) had an average of 72.45. This shows that the average value of the final ability (post-test) was greater than the initial test. After calculating using the Z-test, the calculated Z value was 3.03 and the Z table value was 1.64. When compared, the calculated Z value ≥ Z table. Therefore, it can be concluded that the science learning outcomes of fourth-grade students at SD Negeri 72 Lubuklinggau after implementing the RADEC Learning Model were significantly improved.